Platinum deposition onto g-C3N4 with using of labile nitratocomplex for generation of the highly active hydrogen evolution photocatalysts. (8th March 2022) - Vasilchenko, Danila; Zhurenok, Angelina; Saraev, Andrey; Gerasimov, Evgeny; Cherepanova, Svetlana; Kovtunova, Larisa; Tkachev, Sergey; Kozlova, Ekaterina
Abstract: The chemisorption of the labile dimeric platinum nitratocomplex [Pt2 (μ-OH)2 (NO3 )8 ] 2- onto graphene oxide doped graphitic C3 N4 (g–C3 N4 –GO) was performed for the first time to prepare PtOx /g–C3 N4 –GO composites with ionic platinum species (Pt(II)) bonded with N-donor groups of the g-C3 N4 . The thermal treatment of the obtained composites in the hydrogen atmosphere results in a gradual reduction of Pt(II) species with the formation of Pt/g–C3 N4 –GO photocatalysts. The Pt/g–C3 N4 –GO catalysts paired with TEOA sacrificing agent in an aqueous solution were tested in a photoinduced hydrogen evolution reaction under visible light (λ = 425 nm). The photocatalytic activity of prepared materials strongly influenced by the temperature of the reduction stage so that the maximal rate of H2 evolution was revealed for the catalyst (0.5 wt% of Pt) reduced at 400 °C with a quantum efficiency of 3.0% and rate of HER of 5.1 mmol h −1 per 1 g of photocatalysts. The photocatalytic activity of this sample was much higher than the activity of 0.5% Pt/g–C3 N4 –GO photocatalysts prepared by conventional photoreduction of H2 PtCl6 or reduction of this precursor with NaBH4 . The Pt/g–C3 N4 –GO photocatalyst with Pt concentration of 0.1 wt% was prepared using the described protocol and shown specific activity of about 1.4 mol h −1 per 1 g of Pt outperforming analogous material reported to date. Graphical abstract: Image 1 Highlights: PtOx /g–C3 N4 –GO composites were obtained using dimeric platinum(IV) nitratocomplex. Thermal treatment at 100–400 °C in H2 results in the formation of Pt/g–C3 N4 –GO catalysts. Activity was tested in H2 evolution from triethanolamine water solution (λ = 425 nm). Highest activity (5.1 mmol g −1  h −1 ) was achieved by photocatalyst reduced at 400 °C. 0.1% Pt/g–C3 N4 –GO (400 °C) achieved specific activity of 1.4 mol h −1 per 1 g of Pt.